Frequency-tunable millimeter-wave generation technique based on spectral-filtering of a supercontinuum source - Wong, Jia Haur (2013)
In this paper, we show analytically for the first time that spectral-filtering a supercontinuum source into equally-spaced optical combs with identical comb profile can lead to the generation of frequency-tunable microwave signals. Through simulations, we observe that the frequency of the generated microwave signal can be of any integer multiple of the supercontinuum source's repetition rate which is within the bandwidth of the photodetector used. Using a photodetector with a larger bandwidth enable the generation of millimeter-wave signal.